(untitled) (GIST – Education and Learning Research Journal, 2013)
This paper intends to explain how education can be understood as a process that involves the transmission of culture, knowledge, manners and values; meanwhile, globalization implies an evolving process of constructing a global system of languages. In this way, the relationship between the educational and economic systems can become stronger through processes of bilingual education. In Latin America, bilingualism has its origins in European colonization and has acquired power because of the wide range of opportunities that communication in the contemporary world can offer. Therefore, it has prioritized the necessity of raising the levels of undergraduate and post graduate education. The spread of English within the bilingual model as a possibility for the development of Latin American countries does not constitute a very clear perspective in the sense of guaranteeing the inclusion of the entire population. Indeed, a bilingual model with an ethnocentric tendency has prevailed, which favors the English speaking culture as the model to follow. This perspective opens the possibility to reflect on the use of English as a common framework of reference. It means the construction of multicultural and plurilingual spaces which are able to favor the inclusion and innovation of sectors related to transnational markets.